DEVELOPMENT OF TERMITE COOFFE PLANTATION AGRO-TOURISM IN THE KEMUNING LOR ARJASA VILLAGE 2003-2019 - Lisa Andrianti; Bambang Soepeno; Sugiyanto Sugiyanto; Rully Putri Nirmala Puji (History Education, University of Jember, 2021)
The Termite coffee plantation agro-tourism is agro-tourism which has historical heritage and is used as a tourist attraction. The problems in this research are: (1) What is the background of the establishment of termite coffee plantation agro-tourism?; (2) How was the development of termite plantation agro-tourism in 2003-2019?. The method used in this research is the historical method with stages; heuristics, criticism, interpretation and historiography. The results of this research include in 2003 the establishment of the termap coffee plantation into a tourist destination with the first attraction, namely Villa Termap. In 2008 another attraction was made, namely the Educational Tour which is the second attraction after Villa Termites. The next development in 2012 was the development of the attraction of Wisma Robusta. Initially Wisma Robusta was an employee house. In 2016, Kaffe Termap was founded. Development in 2019 Termite coffee plantation agro-tourism has a special food for sale, namely cassava cheese, a typical drink sold, namely Robusta coffee.